Fuel selection in rufous hummingbirds: ecological implications of metabolic biochemistry. - Suarez, R K (1990)
Hummingbirds in flight display the highest rates of aerobic metabolism known among vertebrates. Their flight muscles possess sufficient maximal activities of hexokinase and carnitine palmitoyltransferase to allow the exclusive use of either glucose or long-chain fatty acids as metabolic fuels during flight. Respiratory quotients (RQ = VCO2/VO2) indicate that fatty acid oxidation serves as the primary energy source in fasted resting birds, while subsequent foraging occurs with a rapid shift towards the use of carbohydrate as the metabolic fuel. We suggest that hummingbirds building up fat deposits in preparation for migration behave as carbohydrate maximizers (or fat minimizers) with respect to the metabolic fuels selected to power foraging flight.